A metal organic foam-derived zinc cobalt sulfide with improved binding energies towards polysulfides for lithium–sulfur batteries. Issue 9 (15th June 2020) - Zhang, Haikuo; Liu, Jinyun; Lin, Xirong; Zhong, Yan; Ren, Jiahao; Wang, Zhilong; Han, Tianli; Li, Jinjin
Abstract: The shuttle effect of polysulfides is a serious issue for lithium–sulfur (Li–S) batteries, because it leads to rapid capacity decay. Herein, we present a metal organic foam-derived ZnCo2 S4 that is capable of forming polar bonds with soluble polysulfides and improving the binding force to suppress the shuttle effect. The ZnCo2 S4 also has a smaller Li ion diffusion barrier energy than ZnCo2 O4 . ZnCo2 S4 grown on conductive carbon cloth facilitates fast electron transfer, while its hierarchical structure accommodates the volumetric expansion of sulfur in Li–S batteries. The ZnCo2 S4 /S cathodes exhibit a stable capacity of 833 mAh g −1 after 100 cycles at 0.1C and a high Coulombic efficiency of 99.9%, along with a high rate-performance after repeated tests; these features indicate a good potential for energy storage applications.